Incidence, recurrence, and prevalence of bacterial vaginosis from acute to chronic HIV infection in a prospective cohort of women in South Africa - Asare, Kwabena; Ngcapu, Sinaye; Osman, Farzana; Vandormael, Alain; Mindel, Adrian; Naicker, Nivashnee; Khanyile, Mlungisi; S. Abdool Karim, Salim; Tomita, Andrew; Garrett, Nigel (Annals of epidemiology, 2023)
Purpose - We investigated the incidence, recurrence, prevalence, and risk factors for bacterial vaginosis (BV) diagnosis starting from acute HIV infection among South African women. - Methods - The Centre for the AIDS Programme of Research in South Africa 002 study tested and treated women for BV (Nugent score 7-10) once/twice annually from acute to chronic HIV infection (2004-2020). We estimated BV incidence as the number of new cases and recurrence as the number of subsequent diagnoses per 100 person-years (PYs). We fitted Anderson-Gil Cox-proportional-hazard regression models to determine factors associated with BV incidence or recurrence. - Results - Of 235 participants, the median age at enrollment was 25 years (Inter Quartile Range [IQR] 22-29). BV prevalence at enrollment was 50.6%. BV incidence was 23.9 cases per 100 PYs, and recurrence was 51.3 cases per 100 PYs. BV incidence/recurrence was associated with younger age (<25 years: adjusted hazard ratio [aHR] 1.70, 95% confidence interval [CI] 1.27-2.27), detectable HIV viral load (aHR 1.54, 95% CI 1.27-1.87) and lower CD4 count (<350 cells/μL: aHR 1.33, 95% CI 1.01-1.76). - Conclusions - Our findings underscore the need for early antiretroviral treatment initiation with diagnostic BV and sexually transmitted infection care, especially among younger women.